2016
DOI: 10.1002/adsc.201500619
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Iodide/tert‐Butyl Hydroperoxide‐Mediated Oxidative Annulation for the Selective Synthesis of N‐Substituted 1,2,3‐Benzotriazine‐4(3H)‐ones Using Nitromethane as the Nitrogen Synthon

Abstract: An ovela nd efficiento xidative annulation of 2-aminobenzamides with nitromethane has been developed for the chemoselective synthesis of N-substituted 1,2,3-benzotriazine-4(3H)-ones in moderate to excellent yields under transitionm etalfree conditions.T wo N À Nb onds were constructed in one pot via C À Nc leavage of nitromethane, which was selectively employed as the nitrogen synthon. Thep reliminary mechanistic studies revealed that this protocolproceeded under hypoiodite catalysis generated in situ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 39 publications
(22 reference statements)
0
17
0
Order By: Relevance
“…1B). By contrast, the reactivity of nitromethane as a nitrogen donor has been scarcely developed (40). It was reported that the electrophilic nitroxyl species (HNO) could be generated through the Nef process (41, 42) (Fig.…”
mentioning
confidence: 99%
“…1B). By contrast, the reactivity of nitromethane as a nitrogen donor has been scarcely developed (40). It was reported that the electrophilic nitroxyl species (HNO) could be generated through the Nef process (41, 42) (Fig.…”
mentioning
confidence: 99%
“…The reaction was carried out as described in the general procedure using 2-amino-N-(2'-methylphenyl)benzamide (6r) (0.100 g, 0.442 mmol), polymer-supported nitrite (0.379 g, containing 1.33 mmol of NO2) and p-toluenesulfonic acid monohydrate (0.252 g, 1.33 mmol). The reaction mixture was stirred at 0 °C for 1 h and then heated to 40 °C for N-(4'-Methylphenyl)-1,2,3-benzotriazin-4(3H)-one (7s) 14 The reaction was carried out as described in the general procedure using 2-amino-N-(4'-methylphenyl)benzamide (6s) (0.285 g, 1.26 mmol), polymer-supported nitrite (1.09 g, containing 3.78 mmol of NO2) and p-toluenesulfonic acid monohydrate (0.719 g, 3.78 mmol). The reaction mixture was stirred at 0 °C for 1 h and then heated to 40 °C for 4 h. The reaction mixture was cooled to room temperature and concentrated in vacuo.…”
Section: N-(2'-methylphenyl)-123-benzotriazin-4(3h)-one (7r) 13bmentioning
confidence: 99%
“…Mp 147-150 °C (lit. 14 N-(4'-Fluorophenyl)-1,2,3-benzotriazin-4(3H)-one (7u) 14 The reaction was carried out as described in the general procedure using 2-amino-N-4'-fluorophenyl)benzamide (6u) (0.0500 g, 0.217 mmol), polymer-supported nitrite (0.187 g, containing 0.652 mmol of NO2) and p-toluenesulfonic acid monohydrate (0.124 g, 0.652 mmol). The reaction mixture was stirred at 0 °C for 1 h and then heated to 40 °C for 4 h. Purification by flash column chromatography, eluting with 30% ethyl acetate in hexane gave N-(4'-fluorophenyl)-1,2,3-benzotriazin-4(3H)-one (7u) (0.0320 g, 60%) as a white solid.…”
Section: N-(2'-methylphenyl)-123-benzotriazin-4(3h)-one (7r) 13bmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the strongly electron-withdrawing nitro (NO 2 ) group, nitromethane (CH 3 NO 2 ) is often used as carbon pro-nucleophile [3] as well as a common solvent. Recently, the reactivity of CH 3 NO 2 as nitrogen donor has been developed further using the mixture of either KI, tBuOOH, CsOAc and AcOH [4] or Tf 2 O, HCOOH and AcOH [5] as activating reagents. The transient nitroxyl species (HNO) was tentatively proposed as the crucial intermediate in such reactions, likely formed from the classical Nef reaction (i. e., acid hydrolysis of CH 2 NO 2 À salt to form H 2 CO and HNO).…”
mentioning
confidence: 99%